Influence of pH variations on zinc oxide nanoparticles and their antibacterial activity. (9th November 2018) - Ribut, Siti Huzaimah; Che Abdullah, Che Azurahanim; Mustafa, Muskhazli; Mohd Yusoff, Mohd Zaki; Ahmad Azman, Siti Noorfazleena
Abstract: Zinc oxide nanoparticles (ZnONPs) were synthesized by the sol-gel method at various pH values. XRD, FTIR, FESEM, UV–vis and PL were accomplished to characterize the structural, functional groups, morphology, and optical properties of the samples. The disk diffusion method was conducted to investigates the antibacterial properties of the ZnONPs. The particle sizes of the ZnONPs synthesized between pH 7-11 was explored vary from 59.56–46.45 nm and mostly in spherical shape. Ultraviolet-visible analysis (UV–vis) also revealed the optical properties with the optical band gap of 3.29, 3.31, 3.33, 3.31 and 3.29 eV correspond to ZnONPs in pH 7-11. While the highest PL spectra of ZnONPs display a blue emission band around 484 nm in the UV range at pH 9. The highest diameter of inhibition zone after 120 h was found at 4.4 ± 0.1 cm at pH 11 of ZnONPs. In this research, the average particles size of ZnONPs and the intensities of the XRD pattern decreases with the increasing pH values. However, with the increasing pH values, the antibacterial activity becomes effective.